Analysis of p27 and cyclin 01 genes in gliomas and meningiomas using molecular genetic, immunohistochemical and immunogold electron microscopic techniques - Farizan, Ahmad (2008)
Meningiomas and gliomas are two most commonly reported brain tumor cases worldwide. These types of tumors might occur due to the disruption of the normal cell cycle which is highly controlled by p27 and cyclin 01 genes. This study was performed to determine the mutational status of p27 and cyclin D1, level of both protein expression and the localization of both proteins at ultrastructural level via analyses of molecular genetic, immunohistochemistry and immunogold electron microscopy respectively. The molecular genetic analysis revealed mutations in exon 4 of cyclin 01 gene but none was detected in other studied regions of exon 5 of cyclin 01 gene and exon 1 and 2 of p27 gene. Five different mutations were detected in 2 glioma (8.0%) and 3 meningioma (11.5%) samples. DNA sequencing for the two gliomas samples revealed the presence of non-sense mutation which resulted to the change of C toT nucleotide at codon 223 (Lys223Lys). In the first glioma sample, we also detected a G base deletion at codon 214 which caused a frameshift mutation (Pro214Arg). In addition to that, we also found two other missense mutations in the second glioma sample. T to C nucleotide changes were detected at codon 215 and codon 217 which caused aspartic acid to Glycine changes in two different loci. Screening of mutations in meningiomas cases revealed 3 cases of non-sense mutations and 3 cases of missense mutations in a total of 3 samples. In all 3 samples, we found 3 cases of C to T nucleotide change which resulted to non-sense mutations at codon 223 (Lys223Lys). In the second and third meningioma samples, we found an additional of T to C nucleotide changes at codon 215 which caused missense mutations (Asp215Giy). Another missense mutation was found at codon 217 which showed T to C nucleotide change in the third meningioma sample. Immunohistochemistry analysis of the same group of samples revealed p27 protein overexpression in all cases including meningiomas (82.6%), low grades gliomas (80.0%) and high grades gliomas (84.6%). We subsequently found high level of cyclin 01 expression in meningiomas (70.8%), equal expression of cyclin 01 in low grades of gliomas (50% are low expressers and 50% are high expressers), and downregulation of the protein in higher grades of gliomas (76.9% were low expressers). lmmunogold electron microscopy analysis of cyclin 01 and p27 proteins showed that both proteins were found to be localized at cytoplasm and nucleus of the cells. Our statistical analysis gave no significant correlation between the presence of cyclin 01 mutations with the downregulation of the protein in both meningiomas (p=0.616) and gliomas (p=0.905).